Can miR-34a be suitable for monitoring sensorineural hearing loss in patients with mitochondrial disease? A case series. (1st December 2020) - Marozzo, Roberta; Pegoraro, Valentina; Dipietro, Laura; Ralli, Massimo; Angelini, Corrado; Di Stadio, Arianna
Abstract: Purpose: We aimed at evaluating the feasibility of using MicroRNA (miR)-34a and miR-29b to detect inner ear damage in patients with mitochondrial disease (MD) and sensorineural hearing loss (SNHL). Material and Methods: Three patients with MD and SNHL and seven healthy control subjects were included in this case series. MD patients underwent pure tone audiometry (PTA), distortion product otoacoustic emission (DPOAE) and auditory brain response tests to investigate the specific cochlear and retrocochlear functions; control patients underwent PTA. MiR-34a and miR-29b were extracted from blood in all subjects included in the study. The expression of miR-34a and miR-29b in MD patients and healthy controls were statistically compared, then the expression of these two miRs was compared with DPOAE values. Results: In MD patients, miR-34a was significantly up-regulated compared to healthy controls; miR-34a and DPOAEs were negatively correlated. Conversely, miR-29b was up-regulated only in the youngest patient who suffered from the mildest forms of MD and SNHL, and negatively correlated with DPOAEs. Conclusion: In MD patients, miR-34a and miR-29b might be a marker of inner ear damage and early damage, respectively. Additional studies on larger samples are necessary to confirm these preliminary results.